Prediction of wave propagation, wind wave effects and energy dissipation nearshore of sungai Sarawak estuary - Siti Zaleha, Kamaluddin (Universiti Malaysia Sarawak (UNIMAS), 2009)
SWAN (Simulation WAves Near shore) is a third generation wave model that is use to investigate the physical parameters of Sungai Sarawak estuary. The investigation includes the prediction of wave propagation, wind wave effects and energy dissipation near shore of Sungai Sarawak estuary. Estuary of Sungai Sarawak faced with the problems of the increments in the sedimentation rate. There have been siltation test result shows that after a sluice construction at the upstream of Sungai Sarawak, it causes the tidal influx decreases and leading to some siltation at both upstream and downstream sides with an average siltation thickness of about 0.3m in a year. For this project, the wave modeling was developed for three (3) scenarios of Annual, Northeast and Southwest monsoon. Other than that, for each of the wave modeling scenarios, both short and long term analysis of waves also have been consider and carried out. The long term wave analysis are using Gumbel and Weibull statistical distribution functions for 30-year of return period. The main results for this project are Hs, Tm01, Dir. and energy dissipation. The results are from the eleven (11) selected area stretches along the Sungai Sarawak estuary